2003
DOI: 10.1002/14651858.cd004443
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone for shock

Abstract: Naloxone improves blood pressure, especially mean arterial blood pressure. However, the clinical usefulness of naloxone to treat shock remains to be determined, and additional randomized controlled trials are needed to assess its usefulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…9 Although the reported cardiac depression and antidiuretic effect of opioids have not consistently been duplicated clinically, the SNS depression has been supported by several clinical studies showing improvement in mean arterial pressure with administration of opioid antagonists. 10 Given the deleterious effect on homeostasis restoration and the association of opioids with greater resuscitation volumes in the current study and in that of Sullivan et al's, 17 judicious administration of opioids is needed. Opioids, in particular morphine, are central to pain control in burn patients.…”
Section: Outcome Variablesmentioning
confidence: 79%
See 2 more Smart Citations
“…9 Although the reported cardiac depression and antidiuretic effect of opioids have not consistently been duplicated clinically, the SNS depression has been supported by several clinical studies showing improvement in mean arterial pressure with administration of opioid antagonists. 10 Given the deleterious effect on homeostasis restoration and the association of opioids with greater resuscitation volumes in the current study and in that of Sullivan et al's, 17 judicious administration of opioids is needed. Opioids, in particular morphine, are central to pain control in burn patients.…”
Section: Outcome Variablesmentioning
confidence: 79%
“…42 Administration of lowdose opioid antagonists such as naloxaone may be another maneuver to help prevent the SNS depression without effecting analgesia. 10 This may be particularly effective during the resuscitation phase. Finally, nonpharmacologic means of dealing with pain such as massage, imagery, and distraction need to be explored more fully to assess their role in analgesia management of the burn patient.…”
Section: Outcome Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Coimbra et al (158) have studied the phosphodiesterase inhibitor, pentoxifylline, already widely used for vascular disease because of its rheologic properties, as a treatment for hemorrhage because it reduces neutrophil activation and adhesion. A Cochrane review recently analyzed data on the opiate antagonist, naloxone, which has been studied based on the finding that central mu, epsilon, kappa, and delta receptors are activated during hemorrhagic shock and inhibit calcium channels; the data suggested that further clinical trials are needed to determine if the beneficial effects on blood pressure by the administration of naloxone result in any durable improvements in survival (159). A common thread across all of these potential agents is that they are already in wide clinical use for other disorders.…”
Section: Alternatives To Conventional Fluid Resuscitationmentioning
confidence: 99%
“…58, 59 Other treatments currently under investigation in children include plasmapheresis, IV immunoglobulins, naloxone, and recombinant bactericidal/permeability-increasing protein. [60][61][62][63] Trauma Patients with hemorrhagic shock require aggressive fl uid resuscitation to treat hypovolemia and require blood products for hypotension that does not rapidly respond to fl uids. Supplemental oxygen is an important adjunct in the setting of anemia.…”
Section: Beyond the Golden Hourmentioning
confidence: 99%